PRRT2 missense mutations cluster near C‐terminus and frequently lead to protein mislocalization. (13th April 2019) - Tsai, Meng‐Han; Nian, Fang‐Shin; Hsu, Mei‐Hsin; Liu, Wei‐Szu; Liu, Yo‐Tsen; Liu, Chen; Lin, Po‐Hsi; Hwang, Daw‐Yang; Chuang, Yao‐Chung; Tsai, Jin‐Wu
Summary: Objective: Variants in human PRRT2 cause paroxysmal kinesigenic dyskinesia (PKD) and other neurological disorders. Most reported variants resulting in truncating proteins failed to localize to cytoplasmic membrane. The present study identifies novel PRRT2 variants in PKD and epilepsy patients and evaluates the functional consequences of PRRT2 missense variations. Methods: We investigated two families with PKD and epilepsies using Sanger sequencing and a multiple gene panel. Subcellular localization of mutant proteins was investigated using confocal microscopy and cell surface biotinylation assay in Prrt2‐transfected cells. Results: Two novel PRRT2 variants, p.His232Glnfs*10 and p.Leu298Pro, were identified, and functional study revealed impaired localization of both mutant proteins to the plasma membrane. Further investigation of other reported missense variants revealed decreased protein targeting to the plasma membrane in eight of the 13 missense variants examined (p.Trp281Arg, p.Ala287Thr, p.Ala291Val, p.Arg295Gln, p.Leu298Pro, p.Ala306Asp, p.Gly324Glu, and p.Gly324Arg). In contrast, all benign variants we tested exhibited predominant localization to the plasma membrane similar to wild‐type Prrt2. Most likely pathogenic variants were located at conserved amino acid residues near the C‐terminus, whereas truncating variants spread throughout the gene. Significance: PRRT2 missense variants clustering at the C‐terminus often lead to protein mislocalization. Failure in protein targeting to the plasma membrane by PRRT2 variants may be a key mechanism in causing PKD and related neurological disorders.